The Role of Forkhead Box Protein M1 in Breast Cancer Progression and Resistance to Therapy. (31st January 2016) - Saba, Raya; Alsayed, Alhareth; Zacny, James P.; Dudek, Arkadiusz Z.
Abstract : The Forkhead box M1 (FOXM1) is a transcription factor that has been implicated in normal cell growth and proliferation through control of cell cycle transition and mitotic spindle. It is implicated in carcinogenesis of various malignancies where it is activated by either amplification, increased stability, enhanced transcription, dysfunction of regulatory pathways, or activation of PI3K/AKT, epidermal growth factor receptor, Raf/MEK/MAPK, and Hedgehog pathways. This review describes the role of FOXM1 in breast cancer. This includes how FOXM1 impacts on different subtypes of breast cancer, that is, luminal/estrogen receptor positive (ER+), expressing human epidermal growth factor receptor 2 (HER2), basal-like breast cancer (BBC), and triple negative breast cancer (TNBC). The review also describes different tested preclinical therapeutic strategies targeting FOXM1. Developing clinically applicable therapies that specifically inhibit FOXM1 activity is a logical next step in biomarker-driven approaches against breast cancer but will not be without its challenges due to the unique properties of this transcription factor.